Surkhet district nutrional status survey (Dec 1987-Jan 1988) - Sullivan, Patrick O (1988)
Using a random cluster sampling technique 1106 children of five years of age or less from a stratifield selecting of 10 out of the 51 panchayats in the Surkhet District of the Mid west Development Region of Nepal were assessed in November/ December 1987. A detailed questionnaire were filled in for child and his or her anthropometric data recorded. The questionnaire included data about the entire household and its occupants, the index child and his or her mother. Information was specifically recorded concerning the index child's health, immune status and standard anthropometry. In addition evidence of Vitamin A deficiency was sought. The third household in each cluster was also subjected to an agricultural questionnaire relating to the amount of land farmed. Its productivity and the household's consumption.